2014
DOI: 10.1215/ijm/1446819301
|View full text |Cite
|
Sign up to set email alerts
|

2-local triple derivations on von Neumann algebras

Abstract: We prove that every (not necessarily linear nor continuous) 2-local triple derivation on a von Neumann algebra M is a triple derivation, equivalently, the set Dert(M ), of all triple derivations on M, is algebraically 2-reflexive in the set M(M ) = M M of all mappings from M into M . 1991 Mathematics Subject Classification. Primary 46L05; 46L40.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…For 1 ≤ p < ∞ and p = 2, Al-Halees and Fleming [1] showed that ℓ p is 2-iso-reflexive. In the setting of B(H), C * -algebras and JB * -triples there exists a extensive literature on different classes of (weak-)2-local of maps (see, for example, [2,3,4,10,11,13,14,19,20,23,31,35,39,40] and [43]).…”
Section: Introductionmentioning
confidence: 99%
“…For 1 ≤ p < ∞ and p = 2, Al-Halees and Fleming [1] showed that ℓ p is 2-iso-reflexive. In the setting of B(H), C * -algebras and JB * -triples there exists a extensive literature on different classes of (weak-)2-local of maps (see, for example, [2,3,4,10,11,13,14,19,20,23,31,35,39,40] and [43]).…”
Section: Introductionmentioning
confidence: 99%
“…Applications can be found in quantum physics and quantum information (cf. [18], [43], [37], [36], [22,Chapter 7], and [16], among many others), and in functional analysis with studies on vector-valued measures on von Neumann algebras and 2-local maps on von Neumann algebras, JBW * -algebras and JBW * -triples (see [20], [3], [4], [13] [14] and [32]).…”
Section: Introductionmentioning
confidence: 99%
“…The Dorofeev-Shertsnev theorem was used in [32] in order to apply the Bunce-Wright-Mackey-Gleason theorem to prove the main result of that paper, namely, that a 2-local triple derivation on a von Neumann algebra is a triple derivation (see the next subsection). In section 3 of this paper, we shall establish the first main result of this paper, namely, a Jordan version of Dorofeev's boundedness theorem (Theorem 3.1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations